Penafsiran Qiwamah dan Nusyuz melalui Tafsir bi al-Ra’yi dalam Perspektif Hukum Keluarga Islam Kontemporer - Muhammad Ihsanuddin, Irfan (PT. Meja Ilmiah Publikasi, 2026)
This study aims to comprehensively examine the meanings and dynamics of the interpretation of the concepts of Qiwamah and Nusyuz through the approach of Tafsir bi al-Ra’yi within the framework of the Qur’anic ayat al-ahkam. The primary focus of this research lies in exploring the role of rational and contextual interpretative methods in constructing a more just and relevant understanding of husband–wife relations within Islamic family law. This research employs a qualitative approach using thematic (maudhu’i) Qur’anic exegesis analysis and library research, complemented by in-depth interviews with Qur’anic exegesis scholars and academics in the field of Islamic law. Data analysis was conducted using a descriptive-analytical method through three stages: data reduction, data display, and conclusion drawing. The findings indicate that Tafsir bi al-Ra’yi provides a space for more contextual reinterpretations of the Qur’anic verses on Qiwamah and Nusyuz by considering the principles of justice, equality, and maqāṣid al-sharī‘ah. This interpretative approach rejects narrow textualism and emphasizes social harmony and balanced roles within family life. Theoretically, this study contributes to the development of contextual exegesis paradigms in the study of ayat al-ahkam, while practically it offers implications for the reformulation of Islamic family law that is responsive to gender justice issues and contemporary social transformations.